Invasion of the coccinellid community associated with a tropical annual agroecosystem. (30th November 2022) - Andow, David A.; Fontes, Eliana M. G.; Pires, Carmen S. S.; Souza, Lucas M.; Paula, Débora P.
Abstract: Detailed understanding of the mechanisms enabling or limiting the impacts of invasive generalist predators is needed. Harmonia axyridis is an invasive generalist coccinellid predator that may have destabilised coccinellid communities worldwide and is an excellent candidate for investigating invasion dynamics. We evaluated four hypotheses: (1) Nine years after being detected in Central Brazil, Ha. axyridis has dominated the coccinellid community. This is facilitated by (2) its broader aphid prey range than the other aphidophagous coccinellids, (3) its superiority as an asymmetrical intraguild predator, and (4) the invasibility of the present coccinellid community. We sampled the invertebrate communities associated with six organic vegetable farms in Brazil during 2017 and 2018, conducted a feeding trial to measure prey niche breadth and overlap, and estimated intra‐ and interspecific interaction strengths corresponding to first‐order Lotka‐Volterra parameters to evaluate the strength of intraguild predation and create a community matrix. We found (1) Ha. axyridis comprised ≤8.3% of the coccinellid community. (2) Hi. convergens had the broadest prey niche and dominated the prey niche of Ha. axyridis . (3) We could not determine from the population data if Ha. axyridis was the dominant intraguild predator because its density was too low and constant. (4) The community matrix indicated that the present‐day coccinellid community was stable. We conclude Ha. axyridis has not become invasive in Central Brazil, in part because it does not have the broadest prey niche breadth and the present coccinellid community is stable to the present perturbation of Ha. axyridis . Abstract : Harmonia axyridis has not dominated the aphidophagous coccinellid community in tropical Brazil 9 years after first detection. Hippodamia convergens had the broadest prey niche and dominated the prey niche of Harmonia axyridis . The community matrix indicated that the present‐day coccinellid community was stable to invasion by Harmonia axyridis .